Human development and interaction in the age of ubiquitous technology - Rahman, Hakikur, 1957-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book is an authoritative reference source for the latest scholarly research on the widespread integration of technological innovations around the globe and examines how human-computer interaction affects various aspects of people's lives"--Provided by publisher.
The contribution(s) of modernization theory to ICT4D research / Sylvain K. Cibangu -- ICT integration in education: potential and challenges / Madhuri V. Tikam -- Information communication technology and the street-level bureaucrat: tools for social equity and progressive activism / Lester Leavitt -- ICT in the Indian classroom / Geeta Nair, Robert Hindle -- Collaborative online learning tools and types: few perspectives of its use in academic library / Sarika Sawant -- Decision-making with big data using open source business intelligence systems / Jorge Bernardino, Pedro Caldeira Neves -- Essential e learning tools, techniques and open courseware for e learners and trainers Sarika Sawant -- ICT as an engine for community participation: an assessment of Uganda's community media / Brian Semujju -- Research dimensions of open innovation in small and medium enterprises / Hakikur Rahman -- Managing seven dimensions of ICT4D projects to address project challenges / Devendra Potnis -- Open innovation in small and medium enterprises: perspectives of developing and transitional economies / Hakikur Rahman -- Open innovation: reaching out to the grass roots through SMEs - exploring issues of opportunities and challenges to reach economic sustainability / Hakikur Rahman -- The absence of one-size-fits-all in the day labour organisations ICT4D designs / Christopher Chepken.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 07/07/2016).
Keywords: Information technology -- Economic aspects; Information technology -- Social aspects; Human-computer interaction; Business intelligence; Community media; Day-labor market; Educational technologies; Online learning; Open innovation; Political activities; Electronic books